Chemodiverse monoterpene indole alkaloids from Kopsia teoi, inhibitory potential against α-amylase, and their molecular docking studies - Muhammad, Muhammad Tahir (Elsevier, 2024)
Diabetes mellitus stands as a metabolic ailment marked by heightened blood glucose levels due to inadequate insulin secretion. The primary aims of this investigative inquiry encompassed the isolation of phytochemical components from the bark of Kopsia teoi, followed by the assessment of their alpha-amylase inhibition. The phytochemical composition of the K. teoi culminated in the discovery of a pair of new indole alkaloids; which are 16-epi-deacetylakuammiline N(4)-methylene chloride (akuammiline) (1), and N(1)-methoxycarbonyl-11-methoxy-12-hydroxy-Delta(14-17)-kopsinine (aspidofractinine) (2), together with five known compounds i.e. kopsiloscine G (aspidofractinine) (3), akuammidine (sarpagine) (4), leuconolam (aspidosperma) (5), N-methoxycarbonyl-12-methoxy-Delta(16, 17)-kopsinine (aspidofractinine) (6), and kopsininate (aspidofractinine) (7). All compounds were determined via spectroscopic analyses. The in vitro evaluation against alpha-amylase showed good inhibitory activities for compounds 5-7 with the inhibitory concentration (IC50) values of 21.7 +/- 1.2, 34.1 +/- 0.1, and 30.0 +/- 0.8 mu M, respectively compared with the reference acarbose (IC50 = 34.4 +/- 0.1 mu M). The molecular docking outputs underscored the binding interactions of compounds 5-7 ranging from -8.1 to -8.8 kcal/mol with the binding sites of alpha-amylase. Consequently, the outcomes highlighted the anti-hyperglycemic attributes of isolates from K. teoi.